The Motivation to Love: Overcoming Spiritual Violence and Sacramental Shame in Christian Churches - Moon, Dawne; Tobin, Theresa (My University, 2016)
Our project examines the movement among conservative Christians to change the conversation around gender, sexuality, sin and love, and to even affirm LGBT identities and sometimes even same-sex marriage. Using one poignant example, we will illustrate how our research has allowed us to develop our thought around our three initial research questions. Our first question pertained to the nature of shame, and how shame is treated differently for LGBT members in conservative churches. We will discuss our latest developments in thinking about the healthy role of shame and how shame malfunctions when applied to LGBT identities and practices as if these are sins. We argue that the toxic effects of sacramental shame make the case that sexual and gender differences are not sinful. Our research addresses questions of broad social interest about what shame is, its value, and its toxic distortions. While healthy shame is the desire to preserve social bonds, and sin creates a rupture in those social bonds, treating homosexuality and transgenderness as sin attacks LGBT people’s capacity to relate to others. Our second question asked how LGBT conservative Christians overcome the violence of sacramental shame. We will discuss the ways that claiming LGBT identity helps conservative Christians to resist the sin narrative so that they can relate wholly to other people without fearing their very capacity to do so. Our third question asked what motivates heterosexual/cisgender conservative Christians to end spiritually violent practices and to love more authentically. Surpassing our original hypothesis that “relationship” in Buber’s sense was what makes the difference, we will discuss how our findings shed light on the distinction between objectifying and relational love.
This presentation was delivered on May 7, 2016 by Dr. Dawne Moon and Dr. Theresa Tobin at the 2016 Self, Motivation, and Virtue Conference, held at the University of Notre Dame, South Bend, Indiana.
Keywords: Philosophy; Sociology